Awareness and reporting of notifiable diseases among private laboratory scientists in Lagos, Southwest Nigeria - Magbagbeola D. Dairo; Salewa Leye-Adebayo; Abimbola F. Olatule (PAGEPress Publications, 2018)
The availability of accurate, up-to-date, reliable and relevant health information on disease notification by medical laboratory practitioners is essential to detecting and responding to epidemic outbreaks. However, information on notification practices of private laboratory scientists are not well documented. This study was conducted to assess the level of awareness and knowledge of Integrated Diseases Surveillance and Response (IDSR), as well as its practice by private laboratory scientists in Lagos State, Nigeria. In a cross-sectional study, 190 respondents from 14 chapters of the Association of Medical Laboratory Scientists in Lagos state were interviewed using a pretested self-administered semi-structured questionnaire to collect information on socio-demographic characteristics, awareness of IDSR and its policy, knowledge of notifiable diseases, practice of IDSR and constraints to reporting notifiable diseases. Data was analyzed using descriptive statistics, Chi-square test and logistic regression at P = 0.05. The mean age of the respondents was 34.0 years with a standard deviation (sd) of ±8.5 years and 65.3% were males. Half (50.0%) of them have ≤ 5 years of working experience with a mean of 7.5±5.8 years. About 8.9% had ever heard of IDSR. About 9.5% had ever seen a disease notification form and 51.1% had good knowledge of IDSR guidelines for the country. Most (86.3%) had never reported a notifiable disease. Lack of knowledge on how to report (56.8%) and inefficiency of the health department (44.7%) were the major reasons given for not reporting. A significant predictor of disease notification was awareness of IDSR (OR= 5.7, CI=1.9-16.7). Private medical laboratory practitioner's awareness and practice of disease notification is poor. A range of interventions including awareness campaign, IDSR training, feedback and logistic support for reporting is recommended to improve reporting practices by private medical laboratory scientists.